DAMPAK SOSIAL PASCA KONFLIK 2016 DI KOTA TANJUNGBALAI - Nuzula, Muhammad Hilmi; Riza, Faisal; Desky, Ahmed Fernanda (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2024)
This research aims to determine the social impact caused by the 2016 conflict in Tanjungbalai City. This caonflict occurred against the background of a protest from an ethnic Chinese woman who lived in front of the Al Maksum Mosque on Jalan Karya, Tanjungbalai City I District, South Tanjungbalai District, south Tanjungbalai District and protested about the volume of the call to prayer by statting that her voice was too loud. The Formulation of the problem in this research is the Social Impact that occurred after the 2016 conflict in the city Tanjungbalai. this research uses qualitative methods with research data collection techniques carried out by interviews, participation and documentation. The theory in this research is Dahrendorf’s theory which states that there are two groups in society depending on who controls the reins of power. The informants inn this study were 12 people consisting of 5 main informants and 7 addutional informants. The results of this research show that the conflict that occurred in 2016 occurred spontaneously and suddenly and was unexpected by the community meanwhile, the social impact caused by the 2016 conflict in Tanjungbalai was the destruction of places of worship, relations between residents felt increasingly starined at the time, each group was wary of each other and suspicion arose between fellow enrich groups after the incident, than the impact of economic activities after the incident. In this case, the city government gtogether with religious and community laders as well as the TNI-POLRI have succeeded in controlling this situation in the not too distantfuture so that life in Tanjungbalai is running normally as usual. The city of Tanjungbalai was designated the city of intorelan as a result of the 2016 conflict but is now no longer the city of Intorelan due to difficulties in achieving harmony between religious communities. This was created because the city government together with religious and community leaders as well as the TNI-POLRI carried out regular communication, mettings and dialogue between religious and ultimately gave rise to a consensus for the parties concerned to maintain balance and national city.